The nuts and bolts of the platelet release reaction. (17th February 2017) - Joshi, Smita; Whiteheart, Sidney W.
Abstract: Secretion is essential to many of the roles that platelets play in the vasculature, e.g., thrombosis, angiogenesis, and inflammation, enabling platelets to modulate the microenvironment at sites of vascular lesions with a myriad of bioactive molecules stored in their granules. Past studies demonstrate that granule cargo release is mediated byS olubleN SFA ttachment ProteinRe ceptor (SNARE) proteins, which are required for granule-plasma membrane fusion. Several SNARE regulators, which control when, where, and how the SNAREs interact, have been identified in platelets. Additionally, platelet SNAREs are controlled by post-translational modifications, e.g., phosphorylation and acylation. Although there have been many recent insights into the mechanisms of platelet secretion, many questions remain: have we identified all the important regulators, does calcium directly control the process, and is platelet secretion polarized. In this review, we focus on the mechanics of platelet secretion and discuss how the secretory machinery functions in the pathway leading to membrane fusion and cargo release.